Fatores determinantes do endividamento e da inadimplência associados à propensão da falência da pessoa física - Silva, Luiz Fernando Soares da (2014)
The indebtedness and default rates are themes that are in constant discussion inside and outside the academic area, being present in many costumers' lives. Socioeconomic factors are not the sole features that present impact on the level of indebtedness and default rates of an individual; other demographic variables, and especially the subject's personality traits also tend to explain costumer's indebtedness and default rates. Thus, the main goal of this study is to identify the main predictor factors of indebtedness and default rates that can contribute to the bankruptcy of the individual, legally known as civil insolvency. Through a descriptive, exploratory and predominantly quantitative research, two distinct studies were developed. The Study 1 was conducted with a sample of 284 individuals, and its results showed that the higher the indebtedness, the higher the default rate of the individual, but it was also showed that the self-control personality trait of the individual has the opposite effect on the level of indebtedness. The study 2, conducted with a sample 200 individuals, highlighted the direct relation of the use of credit cards and notification of payment, materialism and also a person?s subjective concept of wellbeing in the level of indebtedness.